War of Opinions: Humanitarianism and Racism (Case Study of The Palestine-Israel Conflict) - Putra, Agung Suhabi (Eastasouth Institute, 2025)
This study explores the dynamics of the war of opinions within the ongoing Israel-Palestine conflict, which is extensively covered through both mainstream and social media. This longstanding conflict not only involves political and religious aspects but also pits humanitarian and racial issues against each other in the global public sphere. Employing a qualitative method and literature study approach, this research examines the narratives constructed by both parties—Israel and Palestine—and how media framing influences public perception. The findings reveal that media framing and the spread of propaganda on social media have triggered sharp polarization in international society, thereby widening the gap and hindering peaceful resolution. Such opinion polarization creates a black-and-white perception of the conflict, turning humanitarian issues into tools of justification and racism into a form of dehumanization. This study underscores the need for a holistic understanding and clear-headed analysis of the conflict to foster solidarity based on human values rather than identity-based fanaticism.